Cytogenetics of Eudiplozoon nipponicum (Monogenea, Diplozoidae): Karyotype, spermatocyte division and 18S rDNA location - Chmúrčiaková, Nikola; Kašný, Martin; Orosová, Martina (Parasitology international, 2020)
Ectoparasitic monogeneans of the family Diplozoidae have direct and monoxenous life cycle. The cytogenetics of monogeneans in general and diplozoids in particular, is a relatively underexplored area. This is why each new detailed description of a karyotype provides significant information about the evolution of monogenean chromosomes and contributes to a better understanding of phylogenetic relationships within this group. This study offers new data on the chromosomes of Eudiplozoon nipponicum, an invasive parasite of the common carp. This species' karyotype consists of seven pairs of telocentric chromosomes (2n = 14 t). After DAPI staining, we marked heterochromatin blocks on all chromosomes in the pericentromeric region. Silver staining (AgNO3) and staining with fluorescent dye YOYO-1 revealed the presence of one large active nucleolus. Fluorescent in situ hybridization with an 18S rDNA probe revealed one cluster of ribosomal genes at the terminal part of the long arms of chromosome pair No. 7. We compared our results with studies on the phylogenetic relationships of diplozoids which applied a combination of molecular methods and classical morphological characterization and found that the results of our cytogenetic analysis are consistent with the hypothesis that E. nipponicum is more basal member of the family Diplozoidae.
Keywords: buněčné dělení; Carps; Staining and Labeling; spermatocyty; In Situ Hybridization, Fluorescence; RNA ribozomální 18S; Spermatocytes; barvení a značení; cytogenetické vyšetření; karyotyp; Cytogenetic Analysis; fylogeneze; RNA, Ribosomal, 18S; hybridizace in situ fluorescenční; mužské pohlaví; zvířata; kapři; Trematoda; Animals; Cell Division; Male; Phylogeny; Karyotype